Centre and periphery: variations in gendered space among Libyan Jews in the late Ottoman period. Issue 5 (20th October 2018) - Simon, Rachel
ABSTRACT: To what an extent did 'women space' among Libyan Jews refer only to the home and a secluded female environment? Were there any inter-gender contacts except for those among close family relatives? This article examines gendered space among Libyan Jews in the late Ottoman period (mid-nineteenth to early twentieth centuries) in the urban coastal centres and the rural hinterland. It shows that the answers to these questions varied depending on locale, socioeconomic status, foreign influence, cultural development, and the passage of time. The available data indicates that the further one was from the geographical and political 'centre' and the lower one's socioeconomic status, the wider the space each gender held, the more flexible and blurred its boundaries, and the greater the possibilities for inter-gender contacts. The study also explores the elasticity of gendered space and how various groups viewed it, as well as its economic, social and communal rationale, based on indigenous and foreign sources. While the sources, which were mostly composed by men, focus on Jews, it is highly likely that the situation among the Muslim majority and in the region in general was similar.